The fireball ghosts, in three major countries of Southeast Asia culture - Dwi Kurniasih; Krismonita, Fanie Yuniar (SHAHIH: Journal of Islamicate Multidisciplinary, 2023)
The mystical mindset is not only common among Indonesians, who frequently associate all events with the supernatural. In neighboring countries, such as Malaysia and Thailand, there is a belief in the existence of mystical or occult things. This research aims to describe the mystery of Banaspati in ASEAN countries, specifically Indonesia, Thailand, and Malaysia. Furthermore, this study will describe the story of Islamization in Java, which is inextricably linked to the influence of mysticism, one of which is Banaspati. This study employs a descriptive-qualitative methodology with a content analysis strategy. According to the study's findings, Indonesians believe that Banaspati, particularly in Java, is a supernatural ghost or spirit that manifests as a blazing fire with great power. In Thailand. Bong fai phayanak (dragon fireballs) is a supernatural phenomenon that occurs in the Mekong River and is caused by the Mekong River's guardian dragon in October. In Malaysia, it is known as polong or "fireball." People in Malaysia believe that a pod is a form of a mystical pet item of humans who have black magic, which functions to bring disaster to someone they don't like. The community's concept of fire elemental ghosts is related to the beliefs of Buddhists in Thailand and Muslims in Indonesia, especially in Java.